Cambios en la diversidad de aves ante la perturbación de hábitats del sur de Quintana Roo, México - Farías-Rivero, Nancy A.; Ramírez-Barajas, Pablo Jesús; Cedeño-Vázquez, J. Rogelio; Sánchez-Sánchez, Joan; Asselin-Nguyen, Antoine; Macario- Mendoza, Pedro Antonio; Tuz-Novelo, Margarito (Instituto de Ecología, A.C., 2022)
Currently, ecosystems face a great loss of biodiversity due to human disturbances, which has negative effects on ecological processes. To know the state of conservation of an environment, indicator species can be identified, which play an important role in different ecological processes and are sensitive to disturbances. The objective of this study was to determine the diversity of birds in response to different habitat disturbances in the ejido Laguna Om, Quintana Roo, Mexico, by means of counting by points from August to September 2017. We selected sites with different conservation status: Tropical Forest, Lagoon, Road, Pasture, and Invasive Fern habitat. In total 103 species of birds were recorded. We found a greater richness of species in Lagoon and the Road. The abundance patterns of species tolerant to disturbance was greater in disturbed areas. We found greater similarity in the trophic guilds composition shared between the Lagoon and the Tropical Forest, and in those shared between the Invasive Fern habitat and the Road, while the composition in the Pasture did not show similarities with respect to the other habitats. Bird species diversity and composition depend on the structural complexity at the habitat level, rather than the type of disturbance that is associated locally.